Ewing’s sarcoma of the parotid gland: A rare entity with review of the literature - Hayfa Chahdoura; Alia Mousli; Ghaiet el Fidaa Noubigh; Safia Yahyaoui; Rim Abidi; Nasr Chiraz (Rare Tumors, 2024)
Background Ewing’s sarcoma is a rare malignant entity. Extraosseous Ewing’s sarcoma (EES) of the head and neck region is a rare occurrence, and Ewing’s sarcoma of the parotid gland is even rarer. To the best of our knowledge, we reported the first case of extraskeletal ES originating from the parotid gland in the Tunisian literature. Case report We report a rare case of EES of the parotid gland in a 35-year-old female. She presented with left parotid tumefaction. Physical examination revealed solid and fixed mass associated with facial paralysis. Magnetic resonance imaging illustrated a left intra-parotid process occupying the entire gland measuring 42 mm infiltrating the masseter and pterygoid muscles. The patient had a total left parotidectomy with ipsilateral triangular lymph node dissection. The definitive pathological examination and the immunohistochemical staining confirmed a primary peripheral neuroectodermal tumor or PNET with the presence of a specific EWING/PNET-type translocation in 60% of the tumor cells. She had an adjuvant chemotherapy (four cycles of vincristine, doxorubicin, cyclophosphamide alternating with ifosfamide and etoposide) followed by external radiotherapy. Conclusion A clinical and radiological follow-up by cervical MRI was done every 3 months and The 10-month follow-up showed no locoregional and distant recurrence.